Antibacterial activity in the hemolymph of the catarina scallop Argopecten ventricosus - Luna-González, Antonio; Maeda-Martínez, Alfonso; Campa-Córdova, Ángel; Orduña-Rojas, Javier (HIDROBIOLÓGICA, 2017)
We conducted a search for antibacterial peptide like activity in hemolymph of Argopecten ventricosus. Pre-purification of peptides was done by reverse phase HPLC. Hemolymph acidic supernatant was loaded into a column packed with C18 matrix. Stepwise elutions were performed with 5, 50, 80, and 100 % acetonitrile (ACN) in 0.05 % trifluoroacetic acid (TFA) over 550 min at a flow rate of 0.2 ml/min. Absorbance was monitored at 280 nm. Eluted fractions were concentrated under vacuum. Vibrio alginolyticus 138-2 was used as a model to test fractions. Growth inhibition zone were observed at 5 and 50 % ACN. This is the first report of antimicrobial peptide-like activity in hemolymph of a pectinid species.